(untitled) (Research, Society and Development, 2021)
Biochemistry is a fascinating part of Biology that has as its main objective the study of the chemistry of life. However, in high school it is seen by many students as a complex and abstract area. In order to overcome such obstacles, the objective of the present work is the proposal of a practical methodological activity in order to facilitate and instigate students’ learning within the discipline of Biology in High School. In this sense, the proposed practical activity uses simple and low-cost materials to approach the proteolytic identification of proteins with the use of tropical fruit juices such as pineapple, papaya, kiwi and powdered meat tenderizer, in the degradation of gelatin and beef fibers. As it is an activity that does not require the existence of a physical laboratory, students themselves can replicate it in their own homes, being highly recommended nowadays, when classes are following a virtual model, to the detriment of the new coronavirus (SARS-CoV-2). Thus, we believe that the experimental methodological proposal, can facilitate students learning on the proposed theme, awakening its scientific side, promoting the discussion and problematization of hypotheses in carrying out the experiment. Finally, with this practical activity, the teacher can work with students, other subjects of Biology such as Botany and even Animal Physiology of the digestive system.